Evaluation of pigeon pea [Cajanus cajan (L.)] varieties and phosphorus fertilization on drought tolerance mechanisms, grain yield and nutritional value under no-till in a smallholder farming system of South Africa - Malele, Sanari Chalin (My University, 2023)
The first study comprised a survey on pigeon peas to determine the crop’s current status in six local municipalities within the two Provinces. The survey study was divided into two sections. The first section found that the crop is produced on less than 1 ha of land, mostly by old, female, and subsistence farmers, mainly for home consumption. Out of 114 farmers interviewed, 11 were smallholder farmers, 103 subsistence, and no commercial farmers were recorded. Grain yield ranged from 10 to 20 kg ha-1 and fewer farmers produced more than 200 kg ha-1. About 66% of farmers used unknown pigeon pea varieties. The crop is mostly produced in an intercrop system with maize and mangoes without fertilizer applications. Only 3% of male farmers used pigeon pea for fodder. About 78% used pigeon peas for income generation and mainly were male farmers. Majority of farmers confirmed that markets are available both locally and internationally. The second section revealed that low production yields were caused primarily by drought, high temperatures, poor agronomic practices, the use of unimproved seeds, and the outbreak of insect pests and disease. The second study was carried out in smallholder farmers' fields at two locations in Limpopo and Mpumalanga, namely, Ofcolaco and Zoeknog respectively from December 2019 to July 2021 to assess the growth and yield of pigeon pea. The trials were laid out at the two experimental sites as a randomized complete block design (RCBD) in 4 × 2 factorial arrangements with three replications. The two treatment factors were four pigeon pea varieties, namely Komboa; Tumia; Ilonga 14-M2; local landrace, and two levels of P-fertilizers at 0 kg ha-1 and 60 kg ha-1. Shoot biomass ranged from 5375 to 10149 kg ha-1 for all varieties and sampling dates at both locations. Application of P-fertilizer and growth stages (P X DAP) significantly influenced shoot biomass at 180 DAP only at Ofcolaco. Interaction of V x P did not show significant variations in shoot biomass at both locations. At Ofcolaco, P yield in plant tissue ranged from 11.11 to 23.89 kg ha-1 and 15.11 to 41.47 kg ha-1 at 120 and 470 DAP, respectively, whereas at Zoeknog, the range was from 16.73 to 31.09kg ha- 1 and 22.68 to 52.0 kg ha-1 at 120 and 470 DAP, respectively. PRE was reduced by the application of P-fertilizer at 60 kg ha-1. The Ilonga 14-M2 variety and the local landrace produced the lowest grain yield ranging from 618 kg ha-1 to 922 kg ha-1. Komboa produced the highest grain yield of 1136 kg ha-1 and 1431kg ha-1 during the first harvest at Ofcolaco and Zoeknog, respectively. The study revealed that unfertilized plants had a higher HI of 30.64% relative to fertilized plants which attained 27.23% during the first harvest only at Ofcolaco. The third study objective was to identify pigeon pea varieties under P fertilization that are tolerant to drought conditions through root biomass production, stomatal conductance, and water use efficiency (WUE). Across all sampling dates, Ilonga 14- M2 produced the highest root biomass of 3185 and 3867 kg ha-1 at Ofcolaco and Zoeknog, respectively. Significant variations in P-fertilizer application were observed from 150 to 500 DAP at Ofcolaco and Zoeknog only at 500 DAP. Photosynthetic rates ranged from 26.39 to 39.06 (μmol m-2s-1) across varieties. Application of P-fertilizer at 60 kg ha-1 influenced the opening of the stomata for Komboa and controlled in Ilonga 14-M2. Komboa resulted in higher intrinsic-WUE due to higher photosynthesis rates over stomatal conductance. Ilonga 14-M2 had the highest instantaneous-WUE, low photosynthetic and transpiration rates, and able to control their stomatal conductance The interaction effect of V x P in instantaneous -WUE was significant and not significant for intrinsic WUE. The fourth study objective was to assess the effect of pigeon pea variety and Pfertilizer application on the nutritional composition of pigeon pea grain. Protein content ranking was 33.30, 32.81, 23.25%, and 20.84% for Ilonga 14-M2, Tumia, Komboa, and the local varieties, respectively at Zoeknog. P-fertilizer application did not change the nutritive value and mineral elements of pigeon pea grains. Minerals, trace elements, and residual soil nutrients did not differ significantly among varieties, Pfertilizer application, and interactions at both locations. In conclusion, Ilonga 14-M4 proved to be a promising variety for drought tolerance, soil fertility enhancement, high protein content, and satisfactory grain yield even under suboptimal rainfall growing seasons. Komboa variety is recommended for farmers in grain production. Whereas Tumia is a dual-purpose variety The application of P-fertilizer at 60 kg ha-1 enhanced pigeon pea’s drought tolerance and productivity but this was found to be dependent on several factors which extend to growth stage, variety, locality, climatic conditions, soil type, and agronomic management practices.
Thesis (Ph.D. Agriculture (Plant Production)) -- University of Limpopo, 2023
Keywords: Drought; Leaf gasgrain yield; P-fertilizer; P yield; PRE; Proteins; Varieties; Biomass; Residual soil nutrients; WUE; Phosphatic fertilizers; Pigeon pea